SMTK Diaspora sebagai Role Model Penerapan Prinsip-prinsip Moderasi Beragama di Kabupaten Sorong - Aponno, Simon (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
This research aims to analyze the existence of Sorong Diaspora Christian Theological High School as a role model in implementing the principles of religious moderation. This research uses a qualitative method. The results showed that Sorong Diaspora Christian Theological High School emphasized its role as a role model for the application of religious moderation values in schools. This can be shown in the form of an educational curriculum that emphasizes the values of religious moderation such as: emphasis on tolerance, respect for diversity, and a contextual approach in biblical interpretation, development of open attitudes, dialogue, and understanding of human rights and religious freedom, integration of religious moderation values, national commitment, non-violence, and accommodating local culture in the curriculum. Then in the form of the exemplary role of teachers in schools in shaping students as prospective moderate religious leaders. Next is in the form of cooperation with the local government and other institutions that can support the creation of a program to implement the values of religious moderation. By teaching the principles of religious moderation, this school contributes to creating an atmosphere of harmony and peace in Sorong Regency which has religious and cultural diversity.